AB1014 USE OF ETANERCEPT BIOSIMILAR IN JIA: PRELIMINARY EXPERIENCE USING REAL WORLD DATA. (June 2019) - Marinelli, Marco; Marino, Achille; Simonini, Gabriele; Cimaz, Rolando; Giani, Teresa
Abstract : Background: Biosimilars are biological medical drugs that are almost an identical copy of an original drug, manufactured by a different company. Since last year regional regulations have imposed a non-medical switch from reference etanercept (ETN) originator to biosimilar (SB4). We compared treatment survival on SB4 to reference etanercept, assessing efficacy and safety data in our cohort of patients with JIA. Objectives: To review clinical charts of JIA patients, including efficacy and safety of ETN biosimilars after transition from originator. Compliance was also assessed. Methods: This was a retrospective observational study of patients with JIA who switched from reference etanercept to SB4 starting during 2018 in our Pediatric Reumatology Department. Clinical and demographic data were collected from charts and inserted into a dedicated database. relevant data included: age at disease onset, age at first administration and duration of treatment, if patients had remission of disease with etanercept therapy or if there were any relapses, ESR and CRP values before and after etanercept therapy, ESR and CRP values before switch to SB4 and after SB4 onset, any adverse effects or relapses of disease after biosimilar. Results: A total of 14 patients (13F, 1M) were identified. Age at diagnosis ranged from 1 to 12 years. Before ETN, all had received methotrexate. ETN was added for disease activity persistence, and induced remission in all cases but one. SB4 treatment duration ranged from 1 to 11 months. After switch to SB4 no disease recurrence was observed. CRP levels, initially elevated in 8/14 cases, normalized during reference etanercept treatment and remained within normal values in all cases during SB4 treatment. ESR median value initially was 40 mm/h (elevated), normalized during reference etanercept treatment (ESR median value 7 mm/h) and remained within normal values (ESR median value 8 mm/h), in all cases during SB4 except one. No side effects were seen, and all families accepted willingly the new prescription. Conclusion: Our preliminary experience shows that a switch from originator to a biosimilar did not lead to loss of efficacy or new safety signals. Our preliminary results suggest that transitioning from reference etanercept to SB4 is associated with sustained efficacy and no change in the adverse event profile. In conclusion SB4 may provide therapeutically equivalent alternative in pediatric patients with JIA. Disclosure of Interests: None declared